Post-impact dynamic response of sandwich plates with foam and non-metallic honeycomb core - Burlayenko, Vyacheslav. N.; Sadowski, Tomasz (Sapienza Università di Roma, 2011)
A finite element (FE) model has been developed for analyzing the dynamic response of sandwich plates with a postimpact damage inducing core crushing, face sheet damage and core-to-face sheet debonding. Calculation of natural frequencies as well as simulation of strongly nonlinear transient dynamic response of impact-damaged sandwich plates is carried out with the ABAQUS code. The influence of parameters of impact-induced damage on dynamic behavior of sandwich plates with foam and nonmetallic honeycomb cores is discussed.